Pupylation‐Based Proximity Labeling Unravels a Comprehensive Protein and Phosphoprotein Interactome of the Arabidopsis TOR Complex - Shuai Zheng; Leonard Blaschek; Delphine Pottier; Luuk Robin Hoegen Dijkhof; Beyza Özmen; Peng Ken Lim; Qiao Wen Tan; Marek Mutwil; Alexander Sebastian Hauser; Staffan Persson (Advanced Science)
Abstract Target of rapamycin (TOR) is a signaling hub that integrates developmental, hormonal, and environmental signals to optimize carbon allocation and plant growth. In plant cells, TOR acts together with the proteins LST8‐1 and RAPTOR1 to form a core TOR complex (TORC). While these proteins comprise a functional TORC, they engage with many other proteins to ensure precise signal outputs. Although TORC interactions have attracted significant attention in the recent past, large parts of the interactome are still unknown. In this resource study, PUP‐IT is adapted, a fully endogenously expressed protein proximity labeling toolbox, to map TORC protein–protein interactions using the core set of TORC as baits. It is outlined how this interactome is differentially phosphorylated during changes in carbon availability, uncovering putative direct TOR kinase targets. An AlphaFold‐Multimer approach is further used to validate many interactors, thus outlining a comprehensive TORC interactome that includes over a hundred new candidate interactors and provides an invaluable resource to the plant cell signaling community.